1984
DOI: 10.1111/j.1445-2197.1984.tb05327.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Oestrogen Receptors in Meningiomas: Biochemical and Clinicopathological Considerations*

Abstract: Specific progesterone and oestrogen receptor proteins were evaluated by a dextran coated charcoal assay and Scatchard plot analysis in 20 intracranial meningiomas. Eleven tumours (55%) were progesterone receptor (PR) positive (mean 108 fmol/mg cytosol protein), whilst all were oestrogen receptor (ER) negative (ER < 10 fmol/mg cytosol protein). There were no trends to suggest a relationship between epidemiological data (patient age, sex and reproductive status in females) or meningioma location and size and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The sex ratio male/female in our series was 1.1, contrary to meningioma WHO I, consistent with most series in the literature suggesting the inactivity of endocrinological influences in these aggressive variants (29,36,45,51,58,60).…”
Section: Discussionsupporting
confidence: 83%
“…The sex ratio male/female in our series was 1.1, contrary to meningioma WHO I, consistent with most series in the literature suggesting the inactivity of endocrinological influences in these aggressive variants (29,36,45,51,58,60).…”
Section: Discussionsupporting
confidence: 83%
“…Our series which shows a 68.8% male preponderance is consistent, at this point, with most series in the literature. This suggests that the endocrinological influences important in the genesis of benign meningiomas are not active in aggressive variants [15,20,27,29,30,38,40]. Regarding the tumor location, only five cases (31.25%) were basal meningiomas, while the majority of cases were convexity and parasagittal tumors as reported in most series of aggressive meningioma [6,10,27,30,40].…”
Section: Discussionmentioning
confidence: 87%
“…Although the 5-year recurrence rate after total removal is only 3-4% for benign meningiomas, it rises to 35-38% with atypical and 78-84% with anaplastic meningiomas [14,23,27]. 38.5% of our patients originally diagnosed as having atypical meningioma experienced recurrence in spite of total surgical resection within a relatively short period. The histology of recurrence was similarly grade II in two cases, unknown in one case (treated with FSRT), while in the other two cases, it progressed to malignant meningioma.…”
Section: Discussionmentioning
confidence: 96%
“…Benign meningiomas have a high level of progesterone receptor expression relative to atypical and malignant meningiomas. Clinical and histopathologic studies have shown an inverse relationship between progesterone receptor expression level and both WHO grade and recurrence [21][22][23]. Risk for atypical and malignant changes increased with non skull base meningiomas.…”
Section: Discussionmentioning
confidence: 99%